2022
DOI: 10.1111/gwat.13206
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Snowmelt into Daily Estimates of Recharge Using a State‐Space Model of Infiltration

Abstract: A state-space model (SSM) of infiltration estimates daily groundwater recharge using time-series of groundwater-level altitude and meteorological inputs (liquid precipitation, snowmelt, and evapotranspiration). The model includes diffuse and preferential flow through the unsaturated zone, where preferential flow is a function of liquid precipitation and snowmelt rates and a threshold rate, above which there is direct recharge to the water table. Model parameters are estimated over seasonal periods and the SSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…(2016) for a review of Kalman‐based applications in hydrology and to Shapiro et al. (2022), Shapiro and Day‐Lewis (2021), Kang et al. (2018), Kitanidis (2015), Ng et al.…”
Section: Methodsmentioning
confidence: 99%
“…(2016) for a review of Kalman‐based applications in hydrology and to Shapiro et al. (2022), Shapiro and Day‐Lewis (2021), Kang et al. (2018), Kitanidis (2015), Ng et al.…”
Section: Methodsmentioning
confidence: 99%
“…Our work could be extended to formulate the inverse problem using the process model for transient conditions (Equation 5), thus allowing for collection and analysis of samples under changing concentration conditions; this approach could capitalize on additional information available from the timing of breakthrough and evolution of concentration at different locations. The inversion of transient data lends itself to solution using filtering or smoothing approaches similar to the implementations in Shapiro et al (2022) and McAliley et al (2022). Compared to conventional sampling schemes, sampling procedures would require carefully controlled experimental operations and would produce significantly more samples for chemical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid infiltration is widely recognized for different unsaturated soil conditions (Mohammed et al 2018; Nimmo 2021), and process models of rapid infiltration have been formulated (Kung 1990; Dragila and Wheatcraft 2001; Nimmo 2010), the application of these models has required the characterization of complex unsaturated zone processes and their associated parameters. Instead, in this investigation, we use a DDMM of vertical infiltration and groundwater recharge as described in Shapiro and Day‐Lewis (2021) and Shapiro et al (2022). Young (2003) discusses concepts and advantages of applying a DDMM to complex physical processes.…”
Section: Modeling Time‐varying Recharge In Response To Precipitationmentioning
confidence: 99%
“…Therefore, we limit the estimation of the model parameters over a period where meteorological conditions affecting infiltration are stable, and assume the model parameters are constant over this period. Shapiro and Day‐Lewis (2021) and Shapiro et al (2022) demonstrated that the model parameters vary seasonally, and thus, the parameters depend on recent meteorological conditions and need to be updated. In this investigation, parameters are estimated over an observation period up to current time, referred to as the Parameter‐Estimation Window (PEW) (Figure 1).…”
Section: Modeling Time‐varying Recharge In Response To Precipitationmentioning
confidence: 99%
See 1 more Smart Citation